Quenching media effects on martensitic transformation, thermodynamic and structural properties of Cu-Al-Fe-Ti high-temperature shape memory alloy - Yildiz, Koksal; Balci, Esra; Akpinar, Sinan (Springer, 2017)
We investigated the effect of three different quenching medias on martensitic transformation, thermodynamic parameters, phase equilibria, microstructural properties and microhardness values of high-temperature Cu-13.2Al-5.1Fe-1.2Ti (mass%) shape memory alloy by means of differential scanning calorimetry, X-ray diffraction, optical microscopy, scanning electron microscopy and Vicker's microhardness measurements. Thermal analysis indicated that the transformation temperatures and thermodynamic parameters of the alloy changed depending on quenching conditions and the transformation temperature range was proportional to the cooling rate. It was found that the step-quenching treatment improved the operation temperature of alloy. Structural analysis showed that the phase components of the alloy were not affected significantly by the quenching conditions, but elemental analysis also revealed that high cooling rate leads to very significant changes on chemical compositions of the phase components. From microstructural investigations, it was found that the microstructure of alloy included a great number of voids having different sizes and forms and also different precipitates grow in these voids. In particular, it was seen that the step-quenching process caused the formation of new voids in the microstructure. Vicker's microhardness measurements revealed that the microhardness value of the alloy was not influenced markedly by the quenching treatments.
Keywords: Cu-based high-temperature SMA; Quenching; Thermal analysis; Martensitic transformation